Preferences and Utilities for Health States after Treatment of Olfactory Groove Meningioma: Endoscopic versus Open - Yao, Christopher M.; Kahane, Alyssa; Monteiro, Eric; Gentili, Fred; Zadeh, Gelareh; de Almeida, John R. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objectives The purpose of this study is to report health utility scores for patients with olfactory groove meningiomas (OGM) treated with either the standard transcranial approach, or the expanded endonasal endoscopic approach.Design The time trade-off technique was used to derive health utility scores.Setting Healthy individuals without skull base tumors were surveyed.Main Outcome Measures Participants reviewed and rated scenarios describing treatment (endoscopic, open, stereotactic radiation, watchful waiting), remission, recurrence, and complications associated with the management of OGMs.Results There were 51 participants. The endoscopic approach was associated with higher utility scores compared with an open craniotomy approach (0.88 vs. 0.74; p < 0.001) and watchful waiting (0.88 vs.0.74; p = 0.002). If recurrence occurred, revision endoscopic resection continued to have a higher utility score compared with revision open craniotomy (0.68; p = 0.008). On multivariate analysis, older individuals were more likely to opt for watchful waiting (p = 0.001), whereas participants from higher income brackets were more likely to rate stereotactic radiosurgery with higher utility scores (p = 0.017).Conclusion The endoscopic approach was associated with higher utility scores than craniotomy for primary and revision cases. The present utilities can be used for future cost-utility analyses.
Keywords: health utility scores; time trade-off; olfactory groove meningioma; expanded endonasal approach; quality of life